Selection of shielding materials for gamma/X-ray and neutron radiations among the commonly used polymers. (23rd March 2020) - Nagaraja, N.; Manjunatha, H.C.; Seenappa, L.; Sridhar, K.N.; Ramalingam, H.B.
We have studied the X-ray and gamma shielding parameters like mass attenuation coefficient, mean free path, half value layer, tenth value layer, effective atomic numbers, electron density, exposure buildup factors, and specific gamma ray constant in commonly used polymers such as polysterene, polypropylene, polytetrafluroethylene (PTFE), polyvinylchloride (PVC), polychlorotetrafluroethylene (PCTFE). We have also measured X-ray and gamma shielding parameters at different energies such as 170 Tm (0.084 MeV), 137 Cs (0.662 MeV) and 60 Co (1.170, 1.330 MeV) in the same polymers. The measured values agree well with the theoretical values. Neutron shielding parameters such as coherent neutron scattering length, incoherent neutron scattering length, coherent neutron scattering cross section, incoherent neutron scattering cross section, total neutron scattering cross section and neutron absorption cross section are in the same polymers. PCTFE is found to be good shielding material for the gamma/X-ray and neutron radiation.